First report of a blaNDM-producing extensively drug resistant Klebsiella pneumoniae ST437 in Italy - Ranieri, Sofia Chiatamone; Fabbrizi, Vittoria; D’ Amario, Ada Maria; Frascella, Maria Giuseppina; Di Biase, Valeria; Di Francesco, Cinzia; Di Sante, Stefania; De Berardis, Luigino; De Martinis, Massimo; Partenza, Massimo; Chiaverini, Alexandra; Centorotola, Gabriella; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Carbapenemase-producing Klebsiella pneumoniae strains (CP-Kps) have recently been observed to spread rapidly worldwide. New Delhi metallo-β-lactamase (NDM) producing clones of Klebsiella pneumoniae (K. pneumoniae) cause a significant healthcare burden, particularly in Indian sub-continent, where this clone is circulating widely. However, in Italy, data on the incidence of these new clones is limited, and an ST437 NDM-producing K. pneumoniae strain has not been reported to date. A sacral ulcer infection caused by a K. pneumoniae strain was identified in an 85-year-old Italian male patient with several comorbidities. Antimicrobial susceptibility testing revealed an extensive resistance to a wide range of antimicrobials, including novel agents such as cefiderocol and ceftazidime/avibactam. Genomic analysis identified the pathogen as an ST437 K. pneumoniae strain harboring blaNDM-5, blaOXA-232 and blaCTX-M-15 genes. Following the identification of this first case, several infection control measures were implemented in healthcare settings, including direct precautions and reinforcement of standard cross-transmission control measures. The emergence of pathogenic microbial clones carrying new genetic determinants, particularly in a little city, requires prompt diagnosis and therapeutic protocols. An effective infection control system for the early detection and/or control of the transmission of NDM-producing Enterobacteriaceae is also needed. Further investigations are required to better understand the potential transmission routes and evolution of these clones.